3 days to live [compact disc, unabridged] - Patterson, James, 1947-; Swierczynski, Duane; Schweigart, Bill; Hogben, Julie Margaret, 1977- (Hachette Audio, 2023)
3 days to live: A CIA-agent bride is on her European honeymoon when she and her husband are poisoned, leaving her seventy-two hours to take revenge.